ELEMENTS OF ETHNIC EXPERIENCES IN NUSANTARA PROVERBS: A TRANSITIVITY ANALYSIS - Suroto Suroto; Syihabuddin syihabuddin (IKIP Siliwangi, 2023)
This research is focused on analyzing how the Nusantara ethnic group represents their experiences through proverbs. The functional grammar theory of Halliday, specifically the ideational meta-function (transitivity), is used as the analytical framework. Data consisting of 48 Nusantara proverbs were analyzed using the transitivity system. Based on the analysis, the ethnic experiences are realized through three main elements: participants, processes, and circumstances. There are two types of participants: human participants (16%) and nonhuman participants (59%). Experiences in the form of events or actions consist of material process (46%), mental process (10%), verbal process (2%), relational process (38%), and existential process (4%). The circumstance elements include accompaniment (29%) and location (71%). Based on the analysis, it can be concluded that the majority of Nusantara ethnic groups represent their experiences through concrete, observable, and material actions. This provides an opportunity for learners to understand the events expressed through proverbs more easily. Furthermore, the use of nonhuman participants, particularly related to nature, dominates the representation. This indicates that nature is an important aspect of representing life experiences. The relationship between humans and nature in this research is further supported by the finding that the second most frequently used process in proverbs is the relational process.